The regulatory network of ThbZIP1 in response to abscisic acid treatment - Ji, Xiaoyu; Liu, Guifeng; Liu, Yujia; Nie, Xianguang; Zheng, Lei; Wang, Yucheng (Frontiers in Plant Science, 2015)
Previously, a bZIP transcription factor from Tamarix hispida, ThbZIP1, was characterized: plants overexpressing ThbZIP1 displayed improved salt stress tolerance but were sensitive to abscisic acid (ABA). In the current study, we further characterized the regulatory network of ThbZIP1 and the mechanism of ABA sensitivity mediated by ThbZIP1. An ABF transcription factor from T. hispida, ThABF1, directly regulates the expression of ThbZIP1. Microarray analysis identified 1,662 and 1,609 genes that were respectively significantly upregulated or downregulated by ThbZIP1 when exposed to ABA. GO analysis showed that the processes including “response to stimulus”, “catalytic activity”, “binding function”, and “metabolic process” were highly altered in ThbZIP1 expressing plants exposed to ABA. The gene expression in ThbZIP1 transformed plants were compared between exposed to ABA and salt on the genome scale. Genes differentially regulated by both salt and ABA treatment only accounted for 9.75% of total differentially regulated genes. GO analysis showed that structural molecule activity, organelle part, membrane-enclosed lumen, reproduction and reproductive process are enhanced by ABA but inhibited by salt stress. Conversely, immune system and multi-organism process were improved by salt but inhibited by ABA. Transcription regulator activity, enzyme regulator activity and developmental process were significantly altered by ABA but were not affected by salt stress. Our study provides insights into how ThbZIP1 mediates ABA and salt stress response at the molecular level.